2019
DOI: 10.1002/ehf2.12483
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences on peak oxygen uptake in heart failure

Abstract: Women represent nearly half of the adult heart failure (HF) population and they remain underrepresented in HF studies. We aimed to evaluate the evidence about peak oxygen uptake (peak VO2) for clinical stratification in women with HF. This narrative review summarizes (i) the evidence endorsing the value of cardiopulmonary exercise testing for clinical stratification and phenotyping HF population; (ii) the determinants of a person's functional aerobic capacity to understand predicted values for patients with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…There is an inverse relationship between age and exercise capacity, just as women tend to have a lower VO2peak than men. 20 – 22 In fact, muscle mass and strength can be reduced by 30% to 50% between 30 and 80 years of age by the loss of muscle fibers and atrophy of the type II muscle fiber. 23 , 24 Regarding sex, women have smaller left ventricular chambers and lower stroke volumes, 25 lower diastolic compliance, 26 greater prevalence of obesity, 25 and less lean mass than men, 27 which would explain the lower exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an inverse relationship between age and exercise capacity, just as women tend to have a lower VO2peak than men. 20 – 22 In fact, muscle mass and strength can be reduced by 30% to 50% between 30 and 80 years of age by the loss of muscle fibers and atrophy of the type II muscle fiber. 23 , 24 Regarding sex, women have smaller left ventricular chambers and lower stroke volumes, 25 lower diastolic compliance, 26 greater prevalence of obesity, 25 and less lean mass than men, 27 which would explain the lower exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Há uma relação inversamente proporcional entre idade e capacidade ergométrica, assim como a mulheres tendem a ter um VO2pico mais baixo do que os homens. [20][21][22] Na verdade, a massa muscular e a força podem ser reduzidas em 30% a 50% entre os 30 e os 80 anos, pela perda de fibra muscular e atrofia da fibra muscular tipo II. 23,24 Em relação ao sexo, as mulheres têm câmaras ventriculares esquerdas menores e volumes sistólicos mais baixos, 25 enchimento diastólico mais baixo, 26 maior prevalência de obesidade 25 e menor massa magra do que os homens, 27 o que poderia explicar a menor capacidade ergométrica.…”
Section: Artigo Originalunclassified
“…This score should identify high‐risk patients ( Figure ) 72 . The prognostic role of social and economic factors has been shown in recent studies, 20,77 and also, sex differences are important to consider in the treatment of patients 78–83 …”
Section: Co‐morbiditiesmentioning
confidence: 98%
“…72 The prognostic role of social and economic factors has been shown in recent studies, 20,77 and also, sex differences are important to consider in the treatment of patients. [78][79][80][81][82][83] Heart failure and cancer There is a complex and intriguing relationship between HF and cancer. 70,[84][85][86][87] On one hand, patients with HF have a higher occurrence of malignancy due to a combination of underlying shared mechanisms and risk factors.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“… 1 Women are more symptomatic, exhibit worse diastolic dysfunction, more congestion, poorer peripheral oxygen kinetics, or lower arterial compliance than men. 8 , 12 , 13 , 14 , 15 In contrast, women seem to have better survival than men, mainly in data derived from clinical trials, as it has been shown in a pooled‐analysis from the I‐PRESERVE (Irbesartan in Heart Failure with Preserved Ejection Fraction), TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist), and CHARM‐Preserved (Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity) trials, 8 , 16 or in the recent PARAGON‐HF (Prospective Comparison of ARNI with ARB Global Outcomes in Heart Failure with Preserved Ejection Fraction) trial, 14 a finding that is incompletely understood. In contrast, data regarding sex‐related differences in mortality risk from observational studies are more conflicting, and female sex may be related to comparable or even worse outcomes in HFpEF.…”
mentioning
confidence: 99%